Acute physiological responses during crossfit® workouts - Jaime Fernández Fernández; Rafael Sabido Solana; Diego Moya; Jose Manuel Sarabia Marin; Manuel Moya Ramón (Asociación Española de Ciencias del Deporte, 2015)
The aims of the present study were to describe the acute physiological and perceptual response of two typical CrossFit® workouts of the day (WODs) and to investigate whether the physical demands of these WODs meet the criteria laid down by the ACSM to improving and maintaining cardiovascular fitness in healthy adults. Methodology: ten healthy subjects (Age: 30±4.2 years) volunteered to participate in a study including laboratory incremental treadmill test and two CrossFit® WODs (e.g., "Fran" and "Cindy"). Measurements included subjects' oxygen uptake (VO2), heart rate (HR), blood lactate (LA) and ratings of perceived exertion (RPE). Results: significant differences (P<0.001; ES=1.0) were found for average VO2 (34.4±3.5 vs. 29.1±1.1 ml·kg-1·min-1), %VO2max (66.2±4.8 vs, 56.7±6.2%) and EE (318.2±32.5 vs. 121.0±38.5 kcal·min-1; P<0.001; ES=3.8) with "Cindy" workout showing higher values, while "Fran" resulted in significantly time spent above 1 (76.0±29.7 vs, 47.7±21.4 %; P<0.05; ES=0.7). Conclusion:  the acute physiological demands of the CrossFit® WODs analyzed meet the ACSM guidelines for energy expenditure and exercise intensity in healthy adults, although due to the high intensity of the workouts analyzed (90-95% of HRmax; LA values >10 mmol-1; RPE values >8), together with the lack of research in this topic, the safety has not been defined for such programs.